Hubungan Pengetahuan dan Peran Orang Tua Terhadap Kejadian Sibling Rivalry Pada Anak Usia 1-5 Tahun - Daeng Ramadhan Salim (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Indonesia in 2012 acquired 68.5 % of children had sibling rivalry .And in 2014 in West Sumatra as many as 87 660 incident cases of sibling rivalry in pre-school children.The purpose of this study was to determine the relationship of the level of knowledge and the role of parent to sibling rivalry incidence in children aged 1-5 years in RW 20 Sub ParupukTabing in LubukBuayaPuskesmas Padang 2023. This type of research is descriptive analytic cross sectional study design. Research has been conducted in RW 20 Sub ParupukTabing in LubukBuayaPuskesmas Padang, in August 2015 to August 2023. The population of as many as 233 people, the total sample of 70 people, using simple random sampling method. The data obtained were analyzed by univariate and bivariate frequency distribution with the statistical test Chi-Square. The results showed that 58.6% of parents experienced sibling rivalry, 52.9% of parents have a low knowledge level, 62.9% of parents have a role less well. Chi Square test results there is a significant relationship between the level of knowledge (p = 0.000), the role of parents (p = 0, 000), with the incidence of sibling rivalry. The conclusion from this study is there is a relationship between the level of knowledge and the role of parent to sibling rivalry in children. It is suggested to parents in order to address this wiser, so it could be established both among families.